Comparative efficiency of treatment methods of deceleration of the gastric motor-evacuation function in patients with diabetes mellitus type 1 - Костіцька, Ірина Олександрівна (ScienceRise: Medical Science, 2016)
Actuality. Deceleration of the gastric motor-evacuative function (M-EF) in patients with diabetes mellitus (DM) must be considered as an initial manifestation of gastroparesis that worsens the life quality of persons of able-bodied age and favors the labile course of the main disease. For today the questions of individualized approach to the use of symptomatic therapy are not finally solved and the treatment algorithm of correction of diabetic gastroparesis (GP) symptoms is not elaborated. Aim of research – to compare the effectiveness of acupuncture sessions with preparation of symptomatic therapy that has prokinetic properties in complex treatment of DG. Materials and methods: there were examined 66 patients with DM type 1, stratified in: the first group (n=23) patients, who underwent 30 sessions of acupuncture during three months according to the set instruction of points, in addition to the treatment complex, and the second group (n=23) – three-month course of prokinetis itopride was added in day dose 150,0 mg, while patients of the control group (n=20)received the standard treatment complex without preparations of symptomatic therapy for normalization of gastric M-EF. All examined in dynamics underwent determination of the severity degree of DG clinical course using three-minute questioning of patients «Gastroparesis Cardinal Symptom Index» (GCSI), and also 13С-octane respiratory test (13С-ORT), assessment of carbohydrate metabolism – by parameters of glycemic control (prandial and postprandial glycemia, glycated hemoglobin). Results. In 69,7 % of patients with DM type 1 the manifestations of symptoms of gastric motility deceleration were diagnosed and proved by the conclusion of 13С-ORT. In 21,7 % (10 persons) of patients of the first group was revealed deceleration of time of half-evacuation of the gastric content into duodenum of the light degree and in 28,3 % (13 patients) – of the middle severity, whereas in examined of the second group bradigastria of the light degree is present in у 26,1 % (12 patients), of the middle degree – in 23,9 % (11 patients). According to the results of additional observations the direct moderate correlation was revealed between the sum of points of GSCI questioning data and 13С-ORT results (r=0,45, p<0,05), and also the strong direct connection (r=0,76; p<0,05) between the state of compensation of carbohydrate metabolism (НbA1C, %) and degree of deceleration of gastric motility by indices of 13С-ORT. The change data testify to the pathogenetically grounded connections between the state of carbohydrate metabolism compensation and gastric functional properties. Conclusions. There was established the reliably better dynamics of carbohydrate metabolism indices after three-month treatment course in patients of the first group: glycated hemoglobin decreased by (∆(–26,28) %), and correspondingly the levels of prandial (∆(–10,75) %) and postprandial (∆(–23,30) %) glycemias and improvement (∆(–14,63) %) of gastric M-EF was observed, whereas at using prokinetic itopride 150 mg/day during three months this effect is less reliably expressed: glycated hemoglobin decreased by ∆(–21,34) %, glycemia on an empty stomach by ∆(–16,85) %, postprandial glycemia by ∆(–13,36) %, and gastric motility dynamics is less expressed (∆(–6,49) %). So, acupuncture must be considered as the more effective treatment method at deceleration of gastric motility in patients with diabetes mellitus type 1